2019
DOI: 10.3389/fmars.2019.00185
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Impacts of a Black Carbon Wet Deposition Event in Halong Bay, Vietnam

Abstract: Black carbon (BC) is emitted to the atmosphere during biomass, biofuel, and fossil fuel combustion, and leaves the atmosphere via dry or wet deposition on land and on the ocean. On a global scale, wet deposition accounts for about 80% of the total atmospheric BC inputs to the ocean. The input of BC particles to the ocean can enrich surface waters with carbon and associated elements, and owing to high porosity and surface-active properties, BC can alter biogeochemical cycles by sorbing dissolved compounds and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…In a wet deposition study in Halong Bay, Vietnam, the input of atmospheric BC to the ocean resulted in the sorption of various compounds, including dissolved nitrogen and phosphorus from seawater. 15 Such high nutrient-containing particles may be incorporated into marine animals. This observation is supported by our PM 1 data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a wet deposition study in Halong Bay, Vietnam, the input of atmospheric BC to the ocean resulted in the sorption of various compounds, including dissolved nitrogen and phosphorus from seawater. 15 Such high nutrient-containing particles may be incorporated into marine animals. This observation is supported by our PM 1 data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, in contrast to previous investigations on atmospheric PM, high P levels were always detected in our aquatic biological samples (Table , Figure , and Table S1). In a wet deposition study in Halong Bay, Vietnam, the input of atmospheric BC to the ocean resulted in the sorption of various compounds, including dissolved nitrogen and phosphorus from seawater . Such high nutrient-containing particles may be incorporated into marine animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the countries rounding the SCS contributed more than one third of the global BC emissions (Bond et al, 2013). Wet precipitation delivers large amounts of BC to the SCS (Mari et al, 2019). In addition, previous studies have shown that the higher DBC concentrations in the upper 100 m of the SCS (avg.…”
Section: Abundance and Distribution Of Soot In The Northeastern South China Seamentioning
confidence: 99%
“…Free viruses, richer in P than N relative to hprok, could adsorb, like DOM, onto dust particles and constitute a P export source. Indeed, free viruses adsorb onto black carbon particles, possibly reducing viral infection (Mari et al, 2019;Malits et al, 2015). However, particle quality is a determining factor for DOM or microbial attachment, and what has been shown for black carbon particles is not necessarily true for dust particles.…”
Section: F Van Wambeke Et Al: Influence Of Atmospheric Deposition On Biogeochemical Cyclesmentioning
confidence: 99%